Inferior vena cava anomalies: Incidental finding in two cases during computed tomography scan - Mubarak, Mohd Yusof; Izyan, Ismail; Najwa, Paiman (Journal of Kathmandu Medical College, 2017)
Inferior vena cava anomaly is usually asymptomatic. It is rare and commonly detected while performing abdominal imaging for other clinical situations. The anomalies can mimic normal anatomical structures. Thus, the identification of the anomalies is important to avoid complication during abdominal procedures. We report two cases of inferior vena cava anomalies found during Computed Tomography scan of our elective cases.